THE QUR’AN’S UNCONFORMITY TO THE MODERN ARABIC GRAMMAR IN THE CONTEXT OF THE LETTER ?? - Mehmet KILIÇARSLAN (Fırat University, 2019)
There are many usages in the Qur’an unconformable to the modern Arabic grammar are encountered. Abu Ubayda and Sibawayh, one of the founders of the Arabic linguistics, refer to these usages -called as grammatical mistakes by the Orientalists- as allowable usages or flexibility and a richness of language or concurrence to the language followed by the first addresses. In this article, first of all the question of what is the common literary language that Qur’an employs. Secondly, the period in which the Qur’an was revealed and the formative period of Arabic grammar are examined and the question of which one is earlier is addressed. An answer for the question whether the Qur’an had been developed in accordance with Arabic grammar or vice versa has been sought. Type and direction of the interaction between the two is examined. Lastly, in the context of the letter ?? the cases of unconformable usages in the Qur’an are analyzed. In the final analysis we have come to these results: 1- The Qur’an was revealed in the Quraishi dialect which was the common literary language of that time. However, It also gave place to some other dialects. 2- The structure of the sentences in the Qur’an is conformable to the Arabic grammer to a large extent. However, It also adopted the method of structuring sentences out of the grammatical rules and tolerating attitude in the language among the Arabs. 3- The unconformable usages in the Qur’an are not any kind of deficiency. For these usages can be seen in any language as a characteristic of language and a way of beautifying the expression.